Appropriate or appropriative? Diversity ideologies, judgment factors, and condemnation of cultural appropriation - Zhang, Rui; Chao, Melody M.; Cho, Jaee; Morris, Michael W.; Cai, Lawrance Yuejun (Frontiers in Social Psychology, 2025)
Cultural appropriation is a critique of cultural borrowing or outgroup cultural use, typically when a more powerful cultural group adopts cultural elements from a less powerful group. Accusations of appropriation have been fiercely debated in recent years, which raises questions about appropriate vs. appropriative adoption of another group's culture. We propose that these different evaluations hinge in part on diversity ideologies. In four studies of U.S. participants (total N = 1,549), we examined the differing effects of three diversity ideologies (colorblindness, multiculturalism, and polyculturalism) on judgments of common cases of cultural appropriation. We found that multiculturalism was associated with harsher judgment, whereas colorblindness and polyculturalism were associated with more lenient judgment. Additionally, we explored the perception of the costs and benefits involved in cultural appropriation and found the associations between diversity ideologies and judgments to be mediated by perceived misrepresentation, permission, distinctiveness, and honorific intent. We conclude that each diversity ideology makes different trade-offs salient in the perceived costs and benefits of cultural use across groups.